IMPLEMENTASI PEMBELAJARAN SENI RUPA MENGGUNAKAN MEDIA LOOSE PARTS DALAM PEMBELAJARAN BDR PADA ANAK KELOMPOK B.1 - Elnia Regiani; Rahmah; Susi Herlinda (Jurnal Ta'lim : Journal Ilmu Pendidikan dan Ilmu Keguruan, 2021)
This research is motivated by the difficulties of children when learning from home (BDR) during the covid-19 pandemic, where learning is only centered on teachers not on the interest needs of children learning, so there is boredom in children when learning art and less attractive learning media provided by teachers. So that there is no fun atmosphere when learning from home. This research aims to find out the Implementation of Fine Arts Learning Using Loose Parts Media in BDR Learning in Group B.1 Children in TK Tunas Harapan District Salo Kampar Riau Regency. This type of research is descriptive research with a qualitative approach. The data collection techniques used in this study are observation, interviews and documentation. The result of this research is that the implementation of fine art learning using loose parts media has been implemented and running as it should, artinya thatprills seni rupa can be done byusing media Loose Parts in BDR learning.. Based on the results of the research and the purpose of the study, the conclusion of this study is that the Implementation of Fine Arts Learning Using Loose Parts Media in BDR Learning in Children Group B.1 In Tk Tunas Harapan Salo District has been implemented and runs as it should be reviewed from aspect 1) Learning Objectives 2) Learning Materials, 3) Models or methods used 4) Media or sources used, 5) Evaluation of learning.